Variabilidade fenótipica e interação com polinizadores ao longo de um gradiente latitudinal em Zeyheria montana Mart. (Bignoniaceae) - Dias Netto, Catarina Gonçalves [UNESP] (2013)
Plant species are composed by populations with a certain genetic and phenotypic differentiation along its geographical range, determined by biotic and abiotic interactions. Pollinators are considered major agents of selection on floral traits, since these traits, with pollinator traits, shapes the interaction. Thus, population differences in floral traits may be related to geographic variation in pollinators composition. This variation may be presented as a geographic mosaic coevolution, based on the local adaptation of each population to its environment and the coevolution in different directions along the communities, forming selection mosaics. Another aspect of this phenotypic variation considers differences between central and marginal populations, since they can find different environmental conditions. A third pattern associated with geographic variation in traits is the cline, in which certain traits suffer gradual changes among populations, related to changes in the environment. Berg (1960) emphasized the importance of studying variability in floral traits related to floral adaptation. According to her study, variability on floral morphology in specialized plants should have evolved to be decoupled from the great variability exhibited by vegetative traits. Zeyheria montana is a Bignoniaceae from cerrado vegetation with broad geographic distribution that depends on pollinators for reproduction. We aim to evaluate the variation in vegetative and reproductive traits of Z. montana along a latitudinal gradient, focusing on the ecological relationships that determine their interaction with pollinators. We analyzed the correlation between floral and vegetative traits, the degree of variation of both sets of features, clustering among individuals according to similarity in morphometric traits and the influence of each variable in the distribution of individuals. Furthermore, we tested the significance with multivariate analysis of variance...